Field notes contributed by James L. Fuller, June 2, 1992 - Fuller, James L.et al (1992)
List of birds and locations contributed by James L. Fuller. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1992. Plustek - flatbed